Liquisolid Tablets Formulation of Atorvastatin Calcium Using Polyethylene Glycol 400 as Solvent and Some Carrier Materials - Yulias Ninik Windriyati (Universitas Gadjah Mada, 2020)
The dissolution of atorvastatin calcium need to be improved since included BCS Class II drugs with low solubility and high permeability, meaning that the dissolution affects the bioavailability of drugs. This research aimed to develop a formulation of a liquisolid tablet using PEG 400 as a solvent and some carrier materials in various compositions to increase the dissolution of atorvastatin calcium. Different formulations of liquisolid tablets were conducted using different quantities of carrier and coating material for adsorbing liquid solvent to produce a free-flowing and compressible powder. Avicel PH 101, Avicel PH 102, Neusilin US2 were employed as the carrier and Aerosil 200 as the coating material. A disintegrant and lubricant were then added to the formed liquisolid system and compressed into tablets by the direct compressing method. The liquisolid tablets were characterized for their tableting properties and possible drug-excipient interaction by XRD and FTIR analysis. The tableting characteristics of atorvastatin calcium liquisolid tablets were within the acceptable limits criteria. The dissolution of AA4 and NA1 liquisolid tablets was higher compared to marketed tablets. Based on the XRD and FTIR analysis, no interactions between drug and excipient.